2018
DOI: 10.1111/1541-4337.12395
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Health‐Promoting Properties and Eating Quality During Off‐Vine Ripening of Tomatoes

Abstract: Tomato (Solanum lycopersicon L.) fruit is rich in various nutrients, vitamins and health‐promoting molecules. Fresh tomatoes are an important part of the Mediterranean gastronomy, and their consumption is thought to contribute substantially to the reduced incidence of some chronic diseases in the Mediterranean populations in comparison with those of other world areas. Unfortunately, tomato fruit is highly perishable, resulting in important economic losses and posing a challenge to storage, logistic and supply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 108 publications
(262 reference statements)
1
21
1
Order By: Relevance
“…Besides the genetic potential, many authors highlighted a large variability in lycopene and β-carotene concentrations and ratios in dependence of environmental factors, agro-technical processes, ripening stage, harvest and postharvest manipulations both in tomato and watermelon fruits (Abushita et al, 2000; Dumas et al, 2003; Perkins-Veazie and Collins, 2004; Lenucci et al, 2009; Siddiqui et al, 2018).…”
Section: Carotenoid In Tomato and Watermelon Fruitsmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides the genetic potential, many authors highlighted a large variability in lycopene and β-carotene concentrations and ratios in dependence of environmental factors, agro-technical processes, ripening stage, harvest and postharvest manipulations both in tomato and watermelon fruits (Abushita et al, 2000; Dumas et al, 2003; Perkins-Veazie and Collins, 2004; Lenucci et al, 2009; Siddiqui et al, 2018).…”
Section: Carotenoid In Tomato and Watermelon Fruitsmentioning
confidence: 99%
“…In the ordinary tomato cultivar Rio Grande, for instance, a significant variation of AsA and DHA concentrations in the range 67.8–108.0 mg/kg fw and 73.4–152.0 mg/kg fw was reported during ripening (Ilahy et al, 2011), while HLY tomato cultivars showed broader intervals (55.8–180 mg/kg fw and 37.8–213 mg/kg fw for AsA and DHA, respectively). The dynamic of change of total vitamin C (AsA + DHA) was also genotype-dependent, with some cultivars (Rio Grande, HLY18, and HLY13) peaking at the orange-red ripening stage, while Lyco2 showing two peaks at the green–orange and red-ripe stages (Siddiqui et al, 2018). Differences in the total vitamin C and AsA accumulation profiles during ripening were also reported between the “low-AsA” tomato cultivar Ailsa Craig and the “high-AsA” cultivar Santorini, although both displayed a characteristic peak at the breaker stage (Mellidou et al, 2012).…”
Section: Vitamin C In Tomato and Watermelon Fruitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulsed electric fields (PEF) have been also proposed as a non-thermal food-grade technology to improve bioactive compounds biosynthesis and reduce microbial load without deleterious effect on the processed product ( 161 , 187 , 188 ). An increase of 187–212% in GL content in broccoli florets and 111–203% in stalks was reported after exposure to 4 kV/cm for 525 and 1,000 μs ( 161 ).…”
Section: Factors Affecting Gls Synthesis and Accumulationmentioning
confidence: 99%